2013
DOI: 10.1111/1747-0080.12056
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the content of vitamin D compounds in selected samples of Australian eggs

Abstract: Aim The aim of this study was to obtain preliminary indicative data for vitamin D3 (cholecalciferol) and 25‐hydroxycholecalciferol (25OHD3) in Australian chicken egg yolk (Gallus gallus domesticus, Linnaeus, 1758), comparing data with the egg yolk of other species, crocodile (Crocodylus porosus, Schneider, 1801) and salmon (Salmo salar, Linnaeus, 1758). Methods Convenience samples of chicken eggs were obtained from a producer known to fortify feed with 25OHD3 as well as D3 (Brand A; n = 6), a producer with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Authors suggested that sunlight exposure was a likely influence. A previous study in Australia found that egg yolk contained 38% more vitamin D 3 and 300% more 25(OH)D 3 when hen feed was fortified with both vitamin D 3 and 25OH)D 3 [ 8 ]. Feed fortification with only vitamin D 3 also increases the content of both vitamin D 3 and 25(OH)D 3 in eggs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors suggested that sunlight exposure was a likely influence. A previous study in Australia found that egg yolk contained 38% more vitamin D 3 and 300% more 25(OH)D 3 when hen feed was fortified with both vitamin D 3 and 25OH)D 3 [ 8 ]. Feed fortification with only vitamin D 3 also increases the content of both vitamin D 3 and 25(OH)D 3 in eggs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both white fish and eggs available in Australia may provide nutritionally useful amounts of vitamin D; however, conveying this information to consumers is hampered by the lack of Australian food composition data. In addition, 25(OH)D 3 is not recognised in the Australia New Zealand Food Standards Code as contributing to the vitamin D content of foods [ 38 ], despite 25(OH)D 3 being used as a fortificant in animal feed, including in layer poultry farming [ 8 ]. The Food Standards Code states that one serve of a food must contain at least 1 µg of vitamin D for a general “source of” claim, or 2.5 µg of vitamin D for a “good source of” claim [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although D 3 is found in several plants, previous results have come mostly from non-edible leaves rather than the edible portions of the different species, such as fruits or seeds. The hydroxylated metabolite of vitamin D 3 , 25(OH)D 3 , is found in animal products [ 8 , 9 , 10 ] and likely has a greater biological activity than vitamin D 3 itself [ 11 , 12 ]. There is some evidence that vitamin D 3 taken orally is more effective than vitamin D 2 at increasing levels of 25(OH)D [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%